Dermatologic care of patients with differences of sex development - Sarah Gold, BA; Christina Huang, BS; Rakan Radi, MD; Pranav Gupta, MBBS; Eric I. Felner, MD, MS; Jeehea Sonya Haw, MD; Krista Childress, MD; Nancy Sokkary, MD; Vin Tangpricha, MD, PhD; Michael Goodman, MD, MPH; Howa Yeung, MD, MSc (Wolters Kluwer, 2023)
Background:. Differences of sex development (DSD or disorders of sex development) are uncommon congenital conditions, characterized by atypical development of chromosomal, gonadal, or anatomic sex. Objective:. Dermatologic care is an important component of the multidisciplinary care needed for individuals with DSD. This article discusses the most common primary dermatologic manifestations of DSD in addition to the cutaneous manifestations of hormonal and surgical therapies in individuals with DSD. Data sources:. Published articles including case series and case reports on PubMed. Study selections:. Selection was conducted by examining existing literature with a team of multidisciplinary specialists. Methods:. Narrative review. Limitations:. This article was not conducted as a systematic review. Results:. In Klinefelter syndrome, refractory leg ulcers and incontinentia pigmenti have been described. Turner syndrome is associated with lymphatic malformations, halo nevi, dermatitis, and psoriasis. Virilization can be seen in some forms of congenital adrenal hyperplasia, where acne and hirsutism are common. Conclusion:. Dermatologists should consider teratogenic risk for treatments of skin conditions in DSD depending on pregnancy potential. Testosterone replacement, commonly used for Klinefelter syndrome, androgen insensitivity syndrome, 5-alpha reductase deficiency, gonadal dysgenesis, or ovotesticular DSD, may cause acne.